Language Practices in Multilingual Classrooms of Selected Primary Schools in Livingstone - Zambia - Kelvin Mambwe; Milimo Simachenya (PT Mattawang Mediatama Solution, 2023)
This study investigated language practices in multilingual classrooms in selected primary schools of urban areas of Livingstone city in Zambia among teachers and learners. The purpose of the study was to establish the motivations that teachers and learners had for drawing ‘linguistic features’ from Nyanja, Tonga and English languages in negotiating meaning during teaching and learning activities. The study also interrogated the language practices against the legislative prescription of language(s) to be used in the formal classroom situations in Zambia. Using purposive sampling, the data were collected from twenty teachers and twenty pupils through semi-structured interviews as well as direct observations of the twenty lessons. The study shows that learners prefer using linguistic features drawn from the named languages as resources in making meaning and for the purposes of learning. The study also establishes that teachers use Nyanja and English as resources for linguistic inclusiveness in order to facilitate teaching. These findings seem to counter the traditional expectation in education set ups in Zambia in which highly formalised monolingual languages are to be applied in teaching and learning processes. Therefore, the assumption which language policy formulators make regarding the choice of language(s) to be used in a particular locality for a specific function are contested. In this regard, the study augments the current debate on multilingualism which moves away from the traditional conception of named languages used in informing the formulation of the Zambia Education language policy.